Mitochondrial Dysfunction in Cardiovascular Diseases: Potential Targets for Treatment - Yang, Jiaqi; Guo, Qianyun; Feng, Xunxun; Liu, Yang; Zhou, Yujie (Frontiers in Cell and Developmental Biology, 2022)
Cardiovascular diseases (CVDs) are serious problems that threaten public health and are responsible for nearly one-third of global deaths. Mitochondrial dysfunction is accountable for the development of most CVDs. Mitochondria produce adenosine triphosphate (ATP) through oxidative phosphorylation (OXPHOS) and inevitably generate reactive oxygen species (ROS). Excessive ROS cause mitochondrial dysfunction and cell death. Mitochondria can protect against these damages via regulation of mitochondrial biogenesis, mitochondrial dynamics, and mitophagy. In recent years, mitochondria-targeted therapy for CVDs has attracted a lot of attention. Various studies have confirmed that clinical drugs (β-blockers, angiotension converting enzyme inhibitors/ angiotensin receptor-II blockers) against CVDs have mitochondrial protective functions. A growing number of cardiac mitochondrial targets have shown cardioprotective effects in experimental and pre/clinical studies. Here, we briefly introduce the mechanisms of mitochondrial dysfunction and summarize the progression of mitochondrial targets against CVDs, which may provide ideas for experimental studies and clinical trials.